Բայի դիմավոր ձևերը և դրանց գործառական առանձնահատկությունները Ստ. Օրբելյանի «Պատմութիւն տանն Սիսական» երկում - Հերմինե Հարությունյան (ՀՀ ԳԱԱ հրատ.)
“История дома Сисакан” Степаноса Орбеляна написана на грабаре в конце XIII в. Те личные формы глагола, которые встречаются в этом произведении, кроме своего основного, используются и во вторичном значении. Это подтверждается тем, что в средневековой историографии параллельно с регулярными формами грабара были распространены элементы и реалии, характерные для народно-разговорного языка. Stepanos Orbelyan’s “History of the Sisakan House” is written in Grabar at the end of the 13th century. Those personal forms of verbs that are met in this study have secondary functions, besides their primary ones. This shows that besides correct forms of Grabar in the historiography of the Middle ages there existed forms invented by native people.
Keywords: Philology; Linguistics; Language and Literature